Causality Analysis: Economic Growth, Economic Openness, Energy Consumption, and Carbon Dioxide Emission Indonesia - Fattah, Azhima Muhammad; Aminata, Jaka; Susilowati, Indah; Pujiyono, Arief (Media Ekonomi dan Manajemen, 2021)
The purpose of this research is to analyze the causality between economic variables, i.e. economic growth, economic openness, and energy consumption to carbon dioxide emissions, and analyze short-run and long-run connections between research variables in Indonesia during the period 1971 to 2018. This research is using VECM analysis and Granger Causality. The results of the VECM analysis in this research show that in the short-run the variable carbon dioxide emissions in the previous period, economic openness, and energy consumption have a significant effect on carbon dioxide emissions in Indonesia, and in the long run, the variables of economic growth, economic openness, and energy consumption have a significant effect on carbon dioxide emissions in Indonesia. The Granger Causality analysis found a bidirectional causality between energy consumption and carbon dioxide emissions. It also found unidirectional causality between economic growth and carbon dioxide emissions. The recommendations that can be shared are that The Government of Indonesia should be more worried about the degradation in environmental quality in Indonesia as a result of economic development. On the other hand, in achieving sustainable economic development, the Indonesian Government must immediately use energy resources more efficiently and environmentally friendly